P57 Seen and not heard! a qi project to enhance young people's voices in their own care. (18th November 2019) - Taylor, AM; Okereafor, A; Parish, E; Hann, G; Davey, N
Abstract : Aims: This QI project aims to increase the number of patients aged 12-16 offered the opportunity to speak to a doctor alone when seen in the Paediatric Assessment Unit of a busy London hospital. Not only does this promote independence and autonomy, but we know that young people don't always share their problems if spoken to with their parents/carers present. Doctors therefore miss key opportunities to identify and address bullying, eating disorders, self-harm, sexual abuse and gang involvement. Methods: By creating a fishbone diagram and process mapping I formulated a list of possible interventions. I have completed two PDSA cycles thus far both of which aimed to raise awareness of good practice and signpost resources. The PDSA cycles currently being planned are: implementation of a new clerking booklet for patients aged 10-16 years old, posters aimed at young people and parents/carers normalising speaking to a doctor alone and detailing the advantages of doing so, and creation of a dedicated space to speak to young people alone. Results: I am using run chart data to identify change in the proportion of young people given the opportunity to speak to a doctor alone. I have demonstrated an increase after my first two interventions but have not yet managed to sustain this change. By completion of the project I anticipate not only an increase in the number of young people given the opportunity to speak to a doctor alone but also an increase in referrals to other services including child and adult mental health services, youth work and sexual health. Clinicians and young people will become more aware of ancillary services leading to increased access and utilisation ultimately facilitating a reduction in bullying, eating disorders, self-harm, sexual abuse and gang involvement. Conclusion: A considered and multi-faceted approach is required to ensure that doctors consistently offer young people the opportunity to speak without their parent/carer present. Even paediatric doctors lack the confidence and skills to communicate with this group of patients; revision of undergraduate and postgraduate curricula is essential to ensure these skills are developed in current and future doctors.